MODIFIKASI TEKNIK INSISI ABERRANSIA FRENULUM SEBELUM PERAWATAN ORTODONTIK: LAPORAN KASUS - pritama, muhammad_fauzi_adityawan; Dahlia Herawati (Lembaga Penelitian Universitas YARSI, 2025)
Abstract Introduction: High labial frenulum attachment affects periodontal tissue to gingivitis and central diastema that interfere aesthetic function, so frenectomy treatment is needed. Frenectomy with convensional technique using blade had a wide wound because attraction of lip muscles and cause a lot of bleeding. Minimal bleeding can be achieved by modifying frenectomy with Incision Below the Clamp (IBC). The objective of this paper was to report frenectomy treatment with IBC technique can minimize bleeding. Case History: A 21-year-old woman came to the Periodontics Clinic of Prof. Soedomo Dental and Oral Hospital UGM with chief complaint of gapped upper front teeth that interfered appearance. After examination, there was aberration labial frenulum superior cause central diastema. Treatment planned before diastema closure was frenectomy with IBC technique using clamp with parallel positition and attached to labial mucosa, then incision under the clamp to base of vestibule and suturing in mucolabial fold. Discussion: Frenectomy with IBC technique made small wounds on the labial mucosa because the attraction of the orbicularis oris muscle laterally was hold back by clamp and suturing immediately after incision will hold muscle attraction after clamp was release and reduced bleeding. Surgery with few bloods will provide a sense of calm and comfort for patient and dentist. Conclusion: Frenectomy for aberrantia frenulum labialis superior using IBC technique completely remove the frenulum and orthodontic treatment can be continued. Key Words: Aberrant frenulum, frenectomy, Incision Below the Clamp, central diastema, musculus orbicularis oris